Agricultural water management for adaptation and mitigation: tension or co-benefits in achieving global good? - Lefore, N.; Schmitter, Petra (Public Library of Science, 2025)
Water is at the intersection of global agriculture and climate change goals, serving as a resource to address the urgency of adaptation and the promise of mitigation. However, these goals – adaptation to ensure food security, changed practices to support mitigation, and reduced water use in agriculture – are often at odds. The tensions between measures aimed at multiple goals at the same time raise a critical question: Can we simultaneously adapt to and mitigate climate change to achieve global goals in both food and water security? We explore this question through examples of agricultural water management from the SIWI Seminar Series on ‘Water for Food in a Changing Climate’ during Stockholm World Water Week 2025.